Pregnancy-Associated Perivascular Epithelioid Cell Tumor of the Tarsal Navicular: A Case Report. Issue 4 (October 2021) - Smith, Haley E.; Arpey, Nicholas C.; Alexiev, Borislav; Peabody, Terrance D.; Attar, Samer
Abstract : Case: A 30-year-old pregnant woman with perivascular epithelioid cell tumor (PEComa) of the tarsal navicular underwent intralesional curettage with allograft at 30 weeks' gestation. She had an uncomplicated delivery at term and is ambulating without tumor recurrence at 1-year follow-up. Conclusion: PEComas are rare tumors most commonly found in soft tissues but have been reported in bone and are occasionally associated with pregnancy. To the best of our knowledge, this is the first reported case of pregnancy-associated PEComa of bone.